Molecular characterization, phylogenetic analysis and adjuvant effect of channel catfish interleukin-1βs against Streptococcus iniae. Issue 87 (April 2019) - Wang, Erlong; Liu, Tao; Wu, Jie; Wang, Kaiyu; Chen, Defang; Geng, Yi; Huang, Xiaoli; Ouyang, Ping; Lai, Weimin; Ai, Xiaohui
Abstract: Channel catfish is one of the most extensively cultured species worldwide, which is widely used as a classical model for comparative immunology. Interleukin-1β (IL1β) is an immunoregulatory cytokine with the potential to enhance the immune response induced by vaccines in many animals. To characterize the molecular characterization and identify the immunoadjuvant role of channel catfish IL1β, molecular cloning, phylogenetic analysis, and expression of two IL1β genes were performed, the bioactivity of their recombinant proteins (rIL1β1 and rIL1β2) were detected in vitro and their adjuvant effects on a subunit vaccine encoding C5a peptidase (pSCPI) of Streptococcus iniae were evaluated. The results indicated that two IL1βs remained highly conserved possessing five conserved motifs compared with other fish IL1βs, although there were 28 nucleotide differences and 16 amino acid differences between channel catfish IL1β1 and IL1β2. Analysis of the ratios of nonsynonymous (dN) and synonymous (dS) substitutions revealed that fish IL1β genes were subjected to negative/purifying selection with global dN/dS ratios value 0.425. The results of adjuvant effect showed that compared with injection of pSCPI alone, co-injecting pSCPI with both rIL1β1 and rIL1β2 significantly enhanced antibody levels, serum bactericidal activity, lysozyme activity, alternative complement hemolytic activity, and the expression of endogenous IL1β and TNF-α in head kidney and spleen. Although vaccination with rIL1β1 or rIL1β2 failed to offer immunoprotection against S. iniae infection, the RPS (relative percent survival) of pSCPI+rIL1β1 and pSCPI+rIL1β2 groups were both higher than pSCPI alone (RPS, 50%), with 64.26% and 60.71%, respectively. Moreover, pSCPI+rIL1β1+rIL1β2 offered significantly higher ( P  < 0.05) immunoprotection (RPS, 75%) against S. iniae infection than pSCPI alone. Our present results not only enrich the molecular structure study of fish IL1βs but also signify that two recombinant channel catfish IL1βs can be used as potential adjuvants in a subunit vaccine model against bacterial infection, which are of profound importance to prevent and control bacterial disease in channel catfish. Highlights: Fish IL1βs were subjected to negative/purifying selection throughout the evolution. Channel catfish IL1βs were highly conserved with five conserved motifs. Channel catfish IL1βs can be used as molecular adjuvants in subunit vaccine model. rIL1β1 as adjuvant was slightly better than rIL1β2 to enhance the immune response. Co-injection of rIL1β1+rIL1β2 induced higher immune response and immunoprotection.